European interlaboratory comparison of Schmallenberg virus (SBV) real-time RT-PCR detection in experimental and field samples: The method of extraction is critical for SBV RNA detection in semen. (July 2015) - Schulz, Claudia; van der Poel, Wim H. M.; Ponsart, Claire; Cay, Ann Brigitte; Steinbach, Falko; Zientara, Stéphan; Beer, Martin; Hoffmann, Bernd
Molecular methods for the detection of Schmallenberg virus (SBV) RNA were rapidly developed after the emergence of this novel orthobunyavirus in Europe. The SBV epizootic wave has declined, but infectious SBV in SBV RNA–positive semen remains a possible risk for the distribution of SBV. However, the abilities of SBV molecular detection methods used at European laboratories have not yet been assessed, to our knowledge. The performances of extraction and real-time reverse transcription polymerase chain reaction (RT-qPCR) methods used at 27 German and 17 other European laboratories for SBV RNA detection in the matrices of whole blood, serum, tissue homogenate, RNA eluates, and bovine semen were evaluated in 2 interlaboratory trials with special emphasis on semen extraction methods. For reliable detection of viral genome in bovine semen samples, highly effective extraction methods are essential to cope with the potential inhibitory effects of semen components on PCR results. All methods used by the 44 laboratories were sufficiently robust to detect SBV RNA with high diagnostic sensitivity (100%) and specificity (95.8%) in all matrices, except semen. The trials demonstrated that the published recommended semen extraction methods (Hoffmann et al. 2013) and a combination of TRIzol LS with an alternative extraction kit have a considerably higher diagnostic sensitivity to detect SBV RNA in semen up to a detection limit of Cq ≤35 compared to other extraction methods used. A thorough validation of extraction methods with standardized semen batches is essential before their use for SBV RNA detection in bovine semen.